Answer:
- Freeman's additional investment = $135,000
- Heyward's revenue = $235,000
- Jones's withdrawals = $16,500
- Ramirez's beginning assets = $149,000
Step-by-step explanation:
1) Freeman's equity at the beginning of the year = $540,000
Freeman's equity at the end of the year = $930,000
Equity increase = $390,000
Net income increased Freeman's equity by $330,000 (= $570,000 - $240,000)
Withdrawals decreased equity by ($75,000)
So additional investment: $330,000 - $75,000 + F = $390,000
additional investment = F = $135,000
2) Heyward's equity at the beginning of the year = $230,000
Heyward's equity at the end of the year = $455,000
Equity increase = $225,000
Net income increased Heyward's equity by Revenue - $128,000
Withdrawals decreased equity by ($32,000)
Additional investments increased equity by : $150,000
equity increase = net income - withdrawals + additional investments
$225,000 = R - $128,000 - $32,000 + $150,000
$225,000 = R - $10,000 ⇒ R = $235,000
3) Jones's equity at the beginning of the year = $34,000
Jones's equity at the end of the year = $20,000
Equity decrease = ($14,000)
Net income decreased Jones's equity by ($7,500)
Withdrawals decreased equity by W
Additional investments increased equity by : $10,000
equity decrease = net income - withdrawals + additional investments
-$14,000 = -$7,500 - W + $10,000
W = -$7,500 + $10,000 + $14,000 = $16,500
4) Ramirez's equity at the beginning of the year = A - $12,000
Ramirez's equity at the end of the year = $134,000
Equity change = $134,000 - A + $12,000 = $146,000 - A
Net income decreased Ramirez's equity by ($13,000)
Withdrawals decreased equity by $39,000
Additional investments increased equity by : $55,000
equity change = net income - withdrawals + additional investments
$146,000 - A = -$13,000 - $39,000 + $55,000
$146,000 - A = $3,000 ⇒ A = $149,000